1995
DOI: 10.1006/jsco.1995.1035
|View full text |Cite
|
Sign up to set email alerts
|

Confluence of Curried Term-Rewriting Systems

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Now let R be a TRS satisfying UN. Kahrs (1995) has proved preservation of CR, and R CR is CR, therefore PP(R CR ) is CR. We will prove that PP(R) and PP(R CR ) stand in the same relation as do R and R CR .…”
Section: Preservation Of Wcr By Currying Theorem If R Is Wcr Then Ppmentioning
confidence: 95%
See 1 more Smart Citation
“…Now let R be a TRS satisfying UN. Kahrs (1995) has proved preservation of CR, and R CR is CR, therefore PP(R CR ) is CR. We will prove that PP(R) and PP(R CR ) stand in the same relation as do R and R CR .…”
Section: Preservation Of Wcr By Currying Theorem If R Is Wcr Then Ppmentioning
confidence: 95%
“…We also explore connections between currying and modular properties. Kahrs (1995) has recently shown that the Church-Rosser property (CR) is preserved by currying for all rewrite systems. This corrects an error in an earlier version of this paper, which proved preservation of CR for left-linear systems, but claimed a counterexample for non-left linear systems.…”
Section: Introductionmentioning
confidence: 99%
“…That is, we first introduce an explicit program symbol app to denote application and use the symbols S and F solely as constructors. Secondly we stratify the combinators C ∈ {S, F} into sets {C 0 , C 1 , C 2 } of constructors, each of which represent successive partial applications of their underlying combinator C. Although this 'currying' process is well-known from the world of functional programming, the reader may refer to [20,3] for a formal definition of this process in the context of general term rewriting.…”
Section: Encoding the Factorisation Calculusmentioning
confidence: 99%
“…In first-order rewriting, the question whether properties such as confluence and termination are preserved under currying or uncurrying is studied in [5,6,2]. In [6] a currying transformation from (functional) term rewriting systems (TRSs) into applicative term rewriting systems (ATRSs) is defined; a TRS is terminating if and only if its curried form is.…”
Section: Theorem 5 ⇒ R Is Well-founded On Terms Over F If and Only Ifmentioning
confidence: 99%